Concrete Utopias: The Politics of Aesthetic Interventions on Urban Development in Post-War Sri Lanka - de Mel, Neloufer (University of Colombo, 2015)
This paper examines, by analyzing the workshop process, production and audience responses to Walking Paths by the Stages Theatre Company and the Shadow Scenes art exhibition of Colomboscope 2015, the role of art in mediating questions of post-war futures in Sri Lanka. Both aesthetic projects focus on the theme of post-war urban development and decay, whether by highlighting the disciplinary regimes of the walking paths in and around Colombo, or juxtaposing the shell of the Rio building burnt in the ethnic violence of July 1983, as a site of regenerative public art. The following key questions animate the paper: why has urban development/decay become a central theme in this aesthetic work, and why does this topic provide a particularly powerful platform for debates on post-war futures in Sri Lanka? What linkages does this art make between such futures and post-war social justice? What is the role of political satire in this work? Does the laughter this art generates release us to a new, or modified future, or to one we already know and thereby anticipate? In how this art is received by the public, what do we learn about its impact in mediating ideas on social transformation in contemporary Sri Lanka? Drawing on theoretical insights from Jose Munoz's Crusing Utopia (2009), Slavoj Zizek's The Plague of Fantasies (1997), Agamben's essay 'Potentialities' (2000) and Azar Nafisi's Republic of the Imagination (2014) amongst others, the paper contextualizes its answers to the above questions through a broader discussion on the role of art in transitional societies. In particular, it draws on Munoz's argument that queer art carries the potential to activate in us the 'no-longerconscious and the anticipatory illuminations of the not yet conscious' in a manner that uses the past and its traces for a radical re-alignment of the future (p.28). This, however, remains only a potentiality of art. Through a close scrutiny of Walking Paths and the Shadow Scenes exhibition, their politics of expression and discourses on post-war futures, the paper assesses the possibilities and limits of this potential in in the aesthetic work under discussion.
Keywords: Urban development, Sri Lankan English theatre, Art, Political Satire, Postwar futures